Factors affecting motivation of close-to-community sexual and reproductive health workers in low-income urban settlements in Bangladesh: a qualitative study - Mahmud, Ilias; Siddiqua, Sumona; Akhter, Irin; Sarker, Malabika; Theobald, Sally; Rashid, Sabina Faiz (PLOS ONE, 2023)
Close-to-community (CTC) health workers play a vital role in providing sexual and reproductive health services in low-income urban settlements in Bangladesh. Retention of CTC health workers is a challenge, and work motivation plays a vital role in this regard. Here, we explored the factors which affect their work motivation. ...
Gesehen am 03.05.2023